An investigation into the tax consequences for individuals performing work abroad - De Ponte, Celeste Lidia (Rhodes University, Faculty of Commerce, Department of Accounting, 2020)
This thesis considered the income tax implications for South African tax resident individuals who render services abroad. The research included an analysis of the impact that the amendment to the section 10(1)(o)(ii) exemption has on individuals rendering services abroad and companies who send their employees abroad. In doing so, this thesis sought to highlight the key factors for consideration, for both employers and individuals. A doctrinal methodology was applied, and an analysis was carried out of relevant tax legislation, commentary of experts in the field of tax law and the relevant case law of South Africa, the United Kingdom (UK), Australia and the United States of America (US), where relevant. It was established that residency is key to determining the tax liability of a person and has an impact on the relief mechanisms that are available where double taxation arises. In addition, the amendment to section 10(1)(o)(ii) was considered. It was concluded that when rendering services abroad, both the employer and employee need to consider the tax consequences that may arise and highlights the factors which may be relevant. The thesis illustrates that, whilst the R1 million exemption alleviates the double tax consequences to a certain extent, further guidance is needed as to how the R1 million threshold will be calculated.
Keywords: South Africa. Income Tax Act, 1962; Income tax -- Law and legislation -- South Africa; Double taxation -- South Africa; International business enterprises -- Taxation -- Law and legislation -- South Africa